ECONOMIC ASPECT OF HVDC TRANSMISSION SYSTEM FOR INDONESIA CONSIDERATION IN NUCLEAR POWER DEVELOPMENT - Edwaren Liun (Jurnal Pengembangan Energi Nuklir, 2009)
ABSTRAKECONOMIC ASPECT OF HVDC TRANSMISSION SYSTEM FOR INDONESIA CONSIDERATION ON NUCLEAR POWER DEVELOPMENT. As a country with hundreds million people, Indonesia needs to generate large scale power and distribute it to thorough country to improve gross domestic product of the population. In the power transmission domain, the High Voltage Direct Current (HVDC) transmission system should be considered for the next decades concerning any technical and economical problems with HVAC transmission. HVDC transmission system is the answer for the Indonesian condition. This system can connect the high energy potential regions to the high energy demand regions. HVDC is the most efficient to transport energy from one region to another one region. Dismantling and removing assets costs are included to the estimated for capital costs, while the environmental and property costs are the costs of securing designations and resource consents, and valuation and legal advice for the HVDC investment. Although converter terminals are expensive however, for long transmissions HVDC system can compensate the costs over breakeven distance through very efficient transmission system. Efficiency of HVDC is appearing from conductor wire, supporting tower, low energy loses and free space used by route of the transmission line. HVDC system is also free from some problem, concerning stability, inductive and capacitive load components, phase differences and frequency system. In the economic aspect the HVDC capital costs for the transmission options comprise estimates of the cost to design, purchase and construct new HVDC transmission components. While operating and maintenance costs of HVDC assets comprise the costs for replacement the old existing overhead transmission lines, underground and submarine cables, and HVDC converter station components.Keywords: HVDC, energy transport, economic aspect, long distance ABSTRACTASPEK EKONOMI SISTEM TRANSMISI HVDC UNTUK PERTIMBANGAN PEMBANGUNAN PLTN DI INDONESIA. Sebagai negara dengan ratusan juta penduduk, Indonesia perlu membangkitkan listrik skala besar dan mendistribusikannya ke seluruh wilayah untuk meningkatkan produk domestik bruto penduduk. Didalam wilayah kerja transmisi listrik, Sistem Transmisi Arus Searah Tegangan Tinggi (HVDC) perlu dipertimbangkan untuk dekade mendatang berkenaan dengan masalah teknis dan ekonomi pada transmisi HVAC. Sistem transmisi HVDC merupakan jawaban untuk kondisi Indonesia. Sistem ini dapat menghubungkan daerah potensi energi tinggi ke daerah permintaan energi tinggi. HVDC adalah yang paling efisien untuk mengangkut energi dari satu daerah ke daerah lain. Biaya pembongkaran pembersihan aset sudah termasuk kedalam perkiraan biaya modal, sedangkan biaya lingkungan dan properti adalah biaya untuk mengamankan sumber daya, perjanjian, evaluasi dan nasihat hukum bagi investasi HVDC. Meskipun terminal converter mahal, namun sistem transmisi HVDC yang panjang dapat mengkompensasi biaya di atas titik impas jarak melalui sistem transmisi yang sangat efisien. Efisiensi HVDC diperoleh dari kawat konduktor, menara pendukung yang ramping, kehilangan energi rendah dan ruang bebas yang digunakan oleh rute dari saluran transmisi. Sistem HVDC juga bebas dari beberapa masalah yang berkenaan dengan stabilitas, komponen beban induktif dan kapasitif, serta perbedaan fase dan frekuensi sistem. Dalam aspek ekonomi biaya modal HVDC untuk pilihan transmisi terdiri dari estimasi biaya disain, pembelian dan konstruksi komponen transmisi HVDC baru. Sedangkan biaya operasi dan pemeliharaan untuk aset HVDC meliputi penggantian komponen saluran transmisi udara, kabel bawah tanah serta aset jalur laut dan stasiun konversi HVDC yang telah usang.Kata kunci: HVDC, pengankutan energi, jarak jauh, aspek ekonomi